OPTIMIZATION OF OXYGEN.ID SERVICE WITH THE IMPLEMENTATION OF HIGH AVAILABILITY ROUTER HOTSPOTS AND TRANSPARENT BANDWIDTH MANAGEMENT ROUTERS: A CASE STUDY OF PT. INDONESIAN TELEMATICS MORA - Bagus Dwi Pandito; Deni Muharam; Suhendra Anjar Dinata; Sudianto Sudianto; Purwani Husodo (Jurnal Scientia, 2022)
With the increasing demand for public free WIFI hotspot service Oxygen.id causes increased traffic in accessing the free WIFI hotspot Oxygen.id service, which of course can result in decreased access performance for customers. By applying The Virtual Router Redundancy Protocol (VRRP) router method and simple bandwidth management queuing to fix existing problems, an additional load simulation of 1450 bytes was carried out from the PING status on the CMD window, the results found that the VRRP hotspot was still stable compared to the existing hotspot. and at the time of testing the mp4 file download process was 17,555KB. The resulting VRRP hotspot output is 673 kbyte, which is bigger than the existing thinkput hotspot, which is 495 kbyte, while the delay result is smaller for VRRP hotspot 35,422 compared to delaying the existing hotspot, which is 39,693 seconds, with the results of this study proven completion in overcome the traffic of serving the free oxygen.id hotspot wifi which is getting higher and higher